Extrachromosomal MicroDNAs and Chromosomal Microdeletions in Normal Tissues - Shibata, Y.; Kumar, P.; Layer, R.; Willcox, S.; Gagan, J.R.; Griffith, J.D.; Dutta, A.
We have identified tens of thousands of short extrachromosomal circular DNAs (microDNA)in mouse tissues as well as mouse and human cell lines. These microDNAs are 200-400 bp long, derived from unique non-repetitive sequence and are enriched in the 5' untranslated regions of genes, exons and CpG islands. Chromosomal loci that are enriched sources of microDNA in adult brain are somatically mosaic for microdeletions that appear to arise from the excision of microDNAs. Germline microdeletions identified by the "Thousand Genomes" project may also arise from the excision of microDNAs in the germline lineage. We have thus identified a new DNA entity in mammalian cells and provide evidence that their generation leaves behind deletions in different genomic loci.